Analysis of Organizational Design Effectiveness in Enhancing Hospital Performance and Adaptability: A Systematic Review - Ananda Digdoyo; Rinawati Rinawati (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
The complex dynamics of the healthcare environment require hospitals to have an effective organizational design to achieve superior performance and high adaptability. However, integrated evidence on which organizational design elements are most effective and how they relate to performance outcomes and adaptability remains fragmented. To review and synthesize recent empirical evidence on the effectiveness of various organizational designs (e.g., matrix, flat, or network structures) in improving the operational, financial, and clinical performance, as well as the adaptability of hospitals in the face of change. This systematic review will be conducted following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. A systematic literature search will be performed in electronic databases such as PubMed, Scopus, Web of Science, and ProQuest. Observational and experimental studies published in the last 10 years that investigate the relationship between organizational design and hospital performance and/or adaptability will be included. The quality of the studies will be assessed using appropriate critical appraisal tools. A narrative analysis will be conducted to synthesize the findings, and a meta-analysis will be considered if the data permits. (This section will be completed after the review. Example: "Out of 2,350 identified studies, 35 met the inclusion criteria. The synthesis of results indicates that differentiated-yet-integrated designs, as well as lean and decentralized structures, are consistently associated with improved clinical performance and operational efficiency. Meanwhile, a collaborative organizational culture and strong network structures were identified as key factors for enhancing adaptability.") The findings of this review are expected to provide an evidence-based guide for hospital managers and policymakers in redesigning organizational structures. Consequently, adopting proven-effective organizational design elements can be a critical strategy for building hospitals that are not only high-performing but also resilient and adaptive for the future.